Effect of empathy competence on moral sensitivity in Chinese student nurses: the mediating role of emotional intelligence - Fang Liu; Hengyu Zhou; Long Yuan; Ying Cai (BMC, 2023)
Abstract Background Ethical issues may pose challenges to nursing students entering clinical practice. Moral sensitivity can assist them in recognising existing moral situations and then taking adequate action. Identifying the variables associated with moral sensitivity may be useful in preparing to improve nursing students' moral sensitivity. Objectives This study investigated empathy, emotional intelligence, and moral sensitivity in Chinese student nurses to explore the association among these three factors and to verify the mediating function of emotional intelligence in determining the connection between empathy and moral sensitivity. Design This study used a cross-sectional correlational design. Setting and participants Through convenience sampling, 239 fourth-year nursing undergraduates at a university in Western China were enrolled in this study. Methods Nursing students who volunteered to participate in the study completed self-reported scales on empathy, emotional intelligence, and moral sensitivity between September and October 2022. The potential mediating effect was explored using the Process Macro and bootstrap method. Results The nursing students' average scores were 39.62 ± 5.27 on moral sensitivity, 108.21 ± 15.49 on empathy, and 124.41 ± 13.66 on EI. Moral sensitivity was positively correlated with emotional intelligence (r = 0.454, p < 0.001) and empathy (r = 0.545, p < 0.001). Furthermore, empathy exerted a substantial direct effect on nursing students' moral sensitivity (B = 0.1424, p < 0.001). Emotional intelligence could mediate the indirect path from empathy to moral sensitivity. (B = 0.0372, p < 0.001). Conclusion Emotional intelligence mediated the association between empathy and moral sensitivity. Thus, educational activities and programmes placing an emphasis on empathy and emotional intelligence may offer an alternative way to promote moral sensitivity in Chinese student nurses. Implications Nursing educators can organise programmes to improve nursing students' emotional competence and professional values. Early exposure to clinical practice benefits nursing students a lot in terms of building interactions with patients and increasing emotional resonance. In addition, nursing educators should develop situational teaching in nursing ethics courses to help students cope with ethical issues.